Functional Defects and the Influence of Age on the Frequency of CD4+CD25+ T-Cells in Type 1 Diabetes - Brusko, Todd M.; Wasserfall, Clive H.; Clare-Salzler, Michael J.; Schatz, Desmond A.; Atkinson, Mark A. (Diabetes (New York, N.Y.), 2005)
Functional Defects and the Influence of Age on the Frequency of CD4 + CD25 + T-Cells in Type 1 Diabetes Todd M. Brusko 1 , Clive H. Wasserfall 1 , Michael J. Clare-Salzler 1 , Desmond A. Schatz 2 and Mark A. Atkinson 1 1 Department of Pathology, Immunology and Laboratory Medicine, University of Florida, Gainesville, Florida 2 Department of Pediatrics, University of Florida, Gainesville, Florida Address correspondence and reprint requests to Mark A. Atkinson, PhD, Department of Pathology, College of Medicine, University of Florida, ARB-R3-128, 1600 SW Archer Rd., Gainesville, FL 32610-0275. E-mail: atkinsonatufl.edu Abstract CD4 + CD25 + T-cells appear to play a crucial role in regulating the immune response. Therefore, we evaluated the peripheral blood frequency and function of CD4 + CD25 + T-cells in 70 type 1 diabetic patients and 37 healthy individuals. Interestingly, a positive correlation was observed between increasing age and CD4 + CD25 + T-cell frequency in both subject groups. In contrast to previous studies of nonobese diabetic mice and type 1 diabetic patients, similar frequencies of CD4 + CD25 + and CD4 + CD25 +Bright T-cells were observed in healthy control subjects and type 1 diabetic patients of similar age. There was no difference between type 1 diabetic subjects of recent-onset versus those with established disease in terms of their CD4 + CD25 + or CD4 + CD25 +Bright T-cell frequency. However, type 1 diabetic patients were markedly defective in their ability to suppress the proliferation of autologous effector T-cells in vitro. This type 1 diabetes-associated defect in suppression was associated with reduced production of interleukin (IL)-2, γ-interferon, and transforming growth factor-β, whereas other cytokines including those of adaptive and innate immunity (IL-10, IL-1β, IL-6, IL-8, IL-12p70, and tumor necrosis factor-α) were similar in control subjects and type 1 diabetic patients. These data suggest that age strongly influences the frequency of CD4 + CD25 + T-cells and that function, rather than frequency, may represent the means by which these cells associate with type 1 diabetes in humans. APC, allophycocyanin GM-CSF, granulocyte-macrophage colony-stimulating factor IFN-γ, γ-interferon IL, interleukin PE, phycoerythrin Teff, CD4+CD25− effector T-cell TGF, transforming growth factor TNF, tumor necrosis factor Treg, CD4+CD25+ regulatory T-cell Footnotes Accepted February 9, 2005. Received October 20, 2004. DIABETES